Methodology (Technology) - Diyana, Kamarudin (Penerbit UMP, 2017)

(untitled)
This module is developed to assist students in the Research Methodology section for the Social Sciences. This module would mainly cover the research methodology section, although some basic areas such as the problem statement, research question, and hypothesis would also be covered briefly. Students would be able to differentiate between a quantitative research and a qualitative research. Through this module, students would have a basic understanding of what goes into research methodology and its components. One of the features of this module is also research design, where students would be able to choose which design within quantitative or qualitative research methodology that would suit their research purpose. This module consists of theories, examples and student activities consisting of matching and scenarios laid out so that students are able to practice what they have learned.